2010
DOI: 10.1021/ic100869r
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Investigation of Tetraethylammonium Polybromides

Abstract: A large number of polyhalides, especially polyiodides, have been discovered and studied, but definitive studies on polybromides remain scarce. Br(3)(-) is the only monovalent polybromide with a known structure. Higher-order monovalent polybromide anions have been proposed but not structurally confirmed as discrete species. In this study tetraalkylammonium polybromides with molecular formulas R(4)NBr(2x+1) (R = ethyl; x = 1-4) were prepared by reacting tetraalkylammonium monobromide or tribromide salts with gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
109
2
18

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(137 citation statements)
references
References 24 publications
8
109
2
18
Order By: Relevance
“…[9] The first systematic study into higher-order polybromides ([Br 5 ] À -[Br 9 ] À ) in the solid state (quaternary ammonium cations) was undertaken as recently as 2010, and has similarities to the liquid state work presented here that follows a stoichiometric approach. [10] The newly published solid-state structure of a [Br 20 ] 2À polybromide network [11] (already seeing preliminary application as an electrolyte component in a p-type dye-sensitized solar cell) [12] and similar networked structures [13] have reignited interest in the area. Recent work by Haller et al has identified discrete nonabromide [14] and undecabromide anions, [13a] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The first systematic study into higher-order polybromides ([Br 5 ] À -[Br 9 ] À ) in the solid state (quaternary ammonium cations) was undertaken as recently as 2010, and has similarities to the liquid state work presented here that follows a stoichiometric approach. [10] The newly published solid-state structure of a [Br 20 ] 2À polybromide network [11] (already seeing preliminary application as an electrolyte component in a p-type dye-sensitized solar cell) [12] and similar networked structures [13] have reignited interest in the area. Recent work by Haller et al has identified discrete nonabromide [14] and undecabromide anions, [13a] .…”
Section: Introductionmentioning
confidence: 99%
“…[19] Indeed, room temperature ionic liquid (RTIL) systems like 1-ethyl-1-methylpyrrolidinium bromide ([C 2 MPyr]Br) used in tandem with 1-decyl-1-methylpyrrolidinium trifluoromethanesulfonate ([C 10 MPyr]OTf), have been used to sequester polybromide species, such as the [Br 20 ] 2À dianion (vide supra), [11] while the bromide salt of the 1-hexyl-1-methyl-imidazolium cation has been used to form a stable nonabromide anion at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Zudem wurde eine Reihe von Tetraalkylammoniumpolybromiden Raman-spektroskopisch untersucht. [8] Darüber hinaus wurde das erste freie Trifluoridmonoanion mithilfe von Matrixisolationsspektroskopie in Edelgasmatrizen (Argon und Neon) bei ca. 4 K charakterisiert.…”
unclassified
“…[10][11][12] Alle weiteren bekannten Polybromidmonoanionen (Penta-, Hepta-und Nonabromid) wurden nur mithilfe von IR-und/ oder Raman-Spektroskopie charakterisiert, weshalb ihre Strukturen lediglich auf Basis dieser Daten , [7] oder als Polybromidnetzwerke, [7,[14][15][16] [17,18] zur Wasseraufbereitung [19] und in selektiven Bromierungen finden. [20] [8] Allerdings zeigte sich bei dieser früheren Studie, dass die weiteren mçglichen Strukturisomere von B (C 2v ), E (D 3h ) und F (D 4h ) als Übergangszustände oder Sattelpunkte hçherer Ordnung vorliegen (Abbildung 3). Außerdem wurde berechnet, dass keine der geschlossenen Ringstrukturen stabil ist.…”
unclassified
See 1 more Smart Citation